Yosemite's songster : one coyote's story - Wadsworth, Ginger (Yosemite Conservancy, 2013)
Coyote is separated from her mate by a rockfall and searches the park to find him. Sometimes silent, occasionally observed, always watchful, Coyote makes her way from one memorable site to another, singing a lonely song of yips and yowls. Gorgeous watercolor paintings of Yosemite illuminate this ultimately satisfying story, while the text closely observes one of the park's most familiar kind of wild resident.